THE EFFECT OF DISTANCE, TEMPERATUR AND AIR HUMIDITY ON FLIES DENSITY IN TEMPORARY LANDFILL OF KEMASAN VILLAGE KEDIRI CITY - Prasetiowati, Lusi; Indasah; Ema Mayasari (Universitas STRADA Indonesia, 2019)
The density of flies in an area, is greatly influenced by: breeding places, sunlight, temperature and humidity. The density of flies will be high if the temperature is between 20-250C, with the humidity that the fly likes is 90%. The purpose of this study was to determine the effect of distance, temperature and air humidity on flies density in temporary landfill of kemasan village kediri city. Analytical survey research methods with cross sectional approach. The study population was all buildings in the the eastern area of ​​the temporary landfill kemasan village in Kediri City totaling 349 buildings. The sample in this study amounted to 186 buildings with a stratified random samplingtechnique. The independent variable is distance, temperature and humidity while the dependent variable is the density of flies. Data is collected by observation and processed by multiple linear regression statistical tests. The results showed the sampling distance ranging from a radius of 50m, 100m, 200m, 300m, 400m, and 500m. The research temperature was obtained the lowest temperature of 25.50C and the highest temperature of 32.50C. Humidity shows the lowest humidity is 51% and the highest humidity is 82%. The density of flies has the lowest density of 1 animal and the highest density of 20 animals with an average of 9 animals per region. There are Effect of Distance, Temperature and Air Humidity on The Density of Flies in Temporary Landfill Kemasan Village Kediri City 2019 (p value 0.001 <0.005 then H1 is accepted). It was concluded that the density of flies occurs not only due to the factors above but depends on the environmental conditions that exist in the region such of the street vendors. It is expected that the cleaning and gardening service will increase the participation of officials and the community in efforts to reduce the population of flies and there are not even flies in the kemasan area.